Overexpression of Testes-Specific Protease 50 (TSP50) Predicts Poor Prognosis in Patients with Gastric Cancer - Fang Liu; Qinghua Cao; Ni Liu; Changzhao Li; Changxuan You; Chuanxin Liu; Ling Xue; Rongcheng Luo (Gastroenterology Research and Practice)
Purpose. To investigate the expression of TSP50 protein in human gastric cancers and its correlation with clinical/prognostic significance. Methods. Immunohistochemistry (IHC) analysis of TSP50 was performed on a tissue microarray (TMA) containing 334 primary gastric cancers. Western blot was carried out to confirm the expression of TSP50 in gastric cancers. Results. IHC analysis revealed high expression of TSP50 in 57.2% human gastric cancer samples (191 out of 334). However, it was poorly expressed in all of the 20 adjacent nontumor tissues. This was confirmed by western blot, which showed significantly higher levels of TSP50 expression in gastric cancer tissues than adjacent nontumor tissues. A significant association was found between high levels of TSP50 and clinicopathological characteristics including junior age at surgery (P=0.001), later TNM stage (P=0.000), and present lymph node metastases (P=0.003). The survival of gastric cancer patients with high expression of TSP50 was significantly shorter than that of the patients with low levels of TSP50 (P=0.021). Multivariate Cox regression analysis indicated that TSP50 overexpression was an independent prognostic factor for gastric cancer patients (P=0.017). Conclusions. Our data demonstrate that elevated TSP50 protein expression could be a potential predictor of poor prognosis in gastric cancer patients.